The role of feeding as synchronizer of gut microbiota dynamics and its potential contribution to protein digestion in greater amberjack (Seriola dumerili) - Navarro-Guillén, Carmen; Degré Lorentsen, Eirik; Perera, Erick; Yúfera, Manuel; Bakke, Ingrid; Vadstein, Olav (Frontiers in Marine Science, 2024)
Gut microbial communities are highly dynamic and respond to factors such as diet and host metabolism. However, there is limited information about how these responses can generate community dynamics at different time scales, such as circadian rhythms. The aim of the present study was to characterize variations along a daily cycle in the gut microbiota of fish on different feeding regimes. In addition, an estimation of the potential contribution of the gut bacterial community to the digestive process of the fish was assessed. The greater amberjack (Seriola dumerili) was used as experimental species, a promising species for Mediterranean aquaculture. Fish were randomly distributed in two different feeding regimes, in triplicate rearing tanks. Feeding regimes were continuous feeding and time-restricted feeding (three meals per day). Fish feces for RNA-based amplicon sequencing and bacterial proteolytic capacity were sampled along a 24h cycle. Time-restricted fed fish exhibited changes in the composition of the active bacterial community promoted by feeding, thus revealing two types of bacterial community profiles: “pre-feeding” and “active-feeder” profiles. Continuous-fed fish maintained an “active-feeder” community profile throughout the whole day. Bray-Curtis and Sørensen similarity indicated that differences in the composition between the two community profiles were mainly driven by the absence/presence of infrequent ASVs (amplicon variant sequences). The potential proteolytic bacterial activity tended to be higher before feeding. Thus, gut microbiota could be a key factor to understanding fish digestion, playing a role in interactions with host metabolism. In conclusion, our results suggest that feeding pattern and time of sampling are important parameters when assessing the microbiome’s contribution to host metabolism.